Vacuum aspiration in the complex treatment of patients with destructive forms of erysipelas - Vasylevska, L. A. (Modern medical technology, 2021)
The purpose of the study. is to give a clinical evaluation of the effectiveness of vacuum therapy in combination with autodermoplasty in the complex treatment of patients with necrotic erysipelas. Materials and methods of research. 114 case histories of patients who were hospitalized in the center of purulentseptic surgery in the Non profit municipal enterprise «City Hospital № 3» in Zaporizhzhia for the period 2019–2020 were analyzed retrospectively and prospectively. Results. Patients on admission to the clinic underwent surgical treatment, which consisted in opening a purulent lesion, necrectomy. After installation of the vacuum aspirator the general condition and the general state of health of patients considerably improved, already by the 5th day cleaning of a wound and emergence of granulation had been noted. The use of a vacuum device contributed to the dosed pressing of the skin flap to the wound surface, reliable fixation of the skin flap and to some extent – the improvement of local microcirculation. Conclusions. The use of vacuum therapy helps to clean the purulent wound, reduces the first phase of the wound process and potentiates the filling of the wound surface with mature granulation tissue. The use of vacuum therapy provides reliable fixation of skin grafts on the wound surface, eliminates the risk of their displacement in the near future after autodermoplasty